Recycling of silicon powder waste cut by a diamond-wire saw through laser-assisted vacuum smelting. (1st December 2018) - Lu, Tong; Tan, Yi; Li, Jiayan; Deng, Dewei
Abstract: This paper proposes laser granulating technology for recycling harmful silicon powder waste cut by a diamond-wire saw. The silicon block produced by laser was easily melted in a traditional vacuum smelting furnace to form a silicon ingot with a high yield and filling rate, which could reach up to 94.7% and 65.7%, respectively. The removal efficiency of the carbon contamination was 74.2% during laser melting process and reached 86% after 30 min of vacuum smelting. In addition, laser melting process promoted the removal of most metal impurities, such as Al, Na, Ca, Mg, and so on, in the silicon powder waste without introducing any other impurities. The residual impurities could be further removed by vacuum smelting. The experiment revealed that the out capacity of the silicon block melted by a single laser gun was 1.91 kg/h, the energy consumption of laser melting was 2.63 kWh/kg, and the yield of the silicon block exceeded 97% at a laser power of 2000 W, a laser scanning interval of 5 mm, and a scanning speed of 6 mm/s. Therefore, the proposed approach is one of the most simple and efficient silicon powder waste pretreatment methods. Highlights: Laser granulation is proposed for melting silicon powder waste for the first time. Laser melting process doesn't introduce any other impurities in theory. The yield of the silicon block melted by laser exceeded 97%. Granulation can improve the efficiency of the subsequent smelting process.